(untitled) (International Journal of Engineering and Computer Science, 2014)
Cloud computing is a new way of delivering computing resources and services. The health care environment is changing faster than ever before due to the demand of delivering higher quality medical services for less money, and increased competitively between health care services providers. Cloud technology is used to create network between patients, doctors, and healthcare institutions by providing applications, services and also by keeping the data in the cloud. This paper mainly emphasize on challenges, need, benefits and advantages of using Cloud computing in Health Care Systems.